2022
DOI: 10.1093/eurheartj/ehac354
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 inhibition by meclofenamate suppresses Ca2+-dependent triggered arrhythmias

Abstract: Aims Cardiac arrhythmias are a major factor in the occurrence of morbidity and sudden death in patients with cardiovascular disease. Disturbances of Ca2+ homeostasis in the heart contribute to the initiation and maintenance of cardiac arrhythmias. Extrasystolic increases in intracellular Ca2+ lead to delayed afterdepolarizations and triggered activity, which can result in heart rhythm abnormalities. It is being suggested that the Ca2+-activated nonselective cation channel TRPM4 is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…However, in-vivo mouse studies did not find altered resting membrane potentials in Trpm4 KO mice (26), nor in AAV9-induced overexpression of WT Trpm4(27) . On the contrary, a recent study by Vandewiele et al used different pathological pro-arrhythmic mouse models to demonstrate that TRPM4 was partially responsible for a long-lasting inward background current induced by Ca 2+ -overload in cardiomyocytes (28) . Using Trpm4 KO mice or newly proposed TRPM4 inhibitor and the anti-inflammatory drug meclofenamate, these authors could suppress these arrhythmias without overt adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, in-vivo mouse studies did not find altered resting membrane potentials in Trpm4 KO mice (26), nor in AAV9-induced overexpression of WT Trpm4(27) . On the contrary, a recent study by Vandewiele et al used different pathological pro-arrhythmic mouse models to demonstrate that TRPM4 was partially responsible for a long-lasting inward background current induced by Ca 2+ -overload in cardiomyocytes (28) . Using Trpm4 KO mice or newly proposed TRPM4 inhibitor and the anti-inflammatory drug meclofenamate, these authors could suppress these arrhythmias without overt adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TRPM4 has a large distribution in tissues and contributes to numerous physiological processes including cardiac electrical activity [ 9 , 13 ]. At present, very few TRPM4 inhibitors are available and only two studies reported the effect of in vivo acute application of the TRPM4 inhibitors: one with 9-phenanthrol injected in rats which results in reduction in arterial pressure and heart rate [ 55 ]; another with meclofenamate injected in mice which results in QTc reduction on an ECG [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in epilepsy TRPM4 contributes to MC loss and increase seizure susceptibility. Our results are especially important in the light of recent findings identifying TRPM4 as a promising drug target in cardiac arrhythmias[39] especially because it has been shown that this type of arrhythmia is often associated with seizures[40]. Thus TRPM4 might be a common regulator of Ca 2+ dependent excitability both in cardiac myocytes and neurons.…”
Section: Discussionmentioning
confidence: 64%
“…target in cardiac arrhythmias [39] especially because it has been shown that this type of arrhythmia is often associated with seizures [40]. Thus TRPM4 might be a common regulator of Ca 2+ dependent excitability both in cardiac myocytes and neurons.…”
mentioning
confidence: 99%